Raftlin, presepsin levels and thiol-disulfide homeostasis in acute appendicitis: A pilot study - ÖZER, ÖMER FARUK; KOÇYİĞİT, ABDÜRRAHİM; GÜLER, ERAY METİN; ERSOY, YELİZ EMİNE; KOÇYİĞİT, ABDÜRRAHİM; SELEK, ŞAHBETTİN; MERAL, İSMAİL; SÜMBÜL, BİLGE; SÜMBÜL, BİLGE; ÖZER, ÖMER FARUK; SELEK, ŞAHABETTİN; GÜLER, ERAY METİN; et al. (My University, 2018)
Objective: To investigate some of the new inflammatory and oxidative stress markers in acute appendicitis.